Inorganic structure and method for manufacturing inorganic structure

A single crystal-like inorganic structure with a hexagonal crystal system achieves controlled anisotropy in mechanical properties by managing the MUD of specific crystal planes, addressing the challenge of expressing anisotropy in hexagonal crystal system inorganic structures.

JP2025044079APending Publication Date: 2025-04-01OSAKA UNIVERSITY +1

Patent Information

Application Number
JP2023151780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Inorganic structures with hexagonal crystal systems face challenges in expressing anisotropy in mechanical properties, which is crucial for applications like medical implants and mobile bodies.

Method used

A single crystal-like inorganic structure with a hexagonal crystal system is developed, where the Multiple of a Uniform Distribution (MUD) of specific crystal planes is controlled within specific ranges to achieve moderate anisotropy in mechanical properties.

Benefits of technology

The inorganic structure exhibits controlled anisotropy in strength and plastic elongation, balancing the need for high mechanical properties in specific directions while avoiding excessive anisotropy, thus making it suitable for diverse applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044079000001_ABST
    Figure 2025044079000001_ABST
Patent Text Reader

Abstract

To provide an inorganic structure including a crystal structure belonging to a crystal system of a hexagonal system that can develop anisotropy of dynamic characteristics.SOLUTION: An inorganic structure includes a single crystal-like crystal structure that belongs to a crystal system of a hexagonal system. In the inorganic structure, MUD (Multiple of Uniform Distribution) of {1 1 -2 0} plane that is obtained by crystal orientation analysis by an electronic backscatter diffraction method (EBSD) is 7.00 or more and 30.00 or less and MUD of {0 0 0 1} plane is 15.00 or more and 90.00 or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an inorganic structure made of an inorganic material and a manufacturing method thereof, and more particularly to an inorganic structure formed by a layered manufacturing method of additive manufacturing technology (AM) and a manufacturing method thereof. [Background technology]

[0002] Inorganic structures made of metals or ceramics are often used in medical implants such as artificial joints and bone plates, moving objects such as automobiles, aircraft, space-related equipment, and ships, and industrial facilities such as plant equipment and manufacturing equipment. Such inorganic structures may be required to have anisotropic mechanical properties depending on the application.

[0003] For example, when an inorganic structure is applied to a moving body, the mechanical properties required for the inorganic structure differ depending on the part of the moving body to which the inorganic structure is applied. For example, the inorganic structure may be required to have high strength in one direction, and may be required to have deformability rather than strength in another direction.

[0004] In view of this, the present inventors have proposed inorganic structures capable of adjusting mechanical properties in JP-A-2011-136083 (Patent Document 1) and JP-A-2013-94390 (Patent Document 2).

[0005] The structures disclosed in Patent Documents 1 and 2 include a solidified portion formed by melting inorganic powder, and a sintered portion formed by sintering the inorganic powder and bonded to the solidified portion. The sintered portion has gaps inside and has a lower density than a solid material. Therefore, the inorganic structure disclosed in Patent Document 1 can have a lower elastic modulus than a solid inorganic structure. Such an inorganic structure can be formed, for example, by a layered modeling method of additive manufacturing technology AM (Additive Manufacturing). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-136083 A [Patent Document 2] JP 2013-94390 A [Non-patent literature]

[0007] [Non-Patent Document 1] H. Yoshinaga, R. Horiuchi, Deformation mechanisms in magnesium single crystals compressed in the direction parallel to hexagonal axis, Transactions of the Japan Institute of Metals, (1963), Vol. 4, pp. 1-8 [Non-Patent Document 2] M.Kang,N.Dixit,K.Hazeli,K.Xie,K.Hemker,KTRamesh,The mechanical behavior of single crystal and polycrystalline pure magnesium, Mechanics of Materials,(2021),Vol.163,104078 [Non-Patent Document 3] F.Wang,K.Hazeli,KDMolodov,CDBarrett,T.Al-Samman,DAMolodov,A.Kontsos,KTRamesh,H.El Kadiri,SRAgnew,Characteristic dislocation substructure in {1 0 -1 2} twins in hexagonal metals,(2018),Vol.143,pp.81-85 Summary of the Invention [Problem to be solved by the invention]

[0008] Inorganic compounds such as metals and ceramics having a crystal structure belonging to the hexagonal crystal system have anisotropy in mechanical properties due to the low symmetry of the crystal structure. Therefore, an inorganic structure made of an inorganic compound having a crystal structure belonging to the hexagonal crystal system may be able to exhibit anisotropy in mechanical properties to an appropriate extent.

[0009] An object of the present disclosure is to provide an inorganic structure having a crystal structure belonging to a hexagonal crystal system capable of exhibiting anisotropy in mechanical properties. [Means for solving the problem]

[0010] The inorganic structure according to the present disclosure is a single-crystal-like inorganic structure having a crystal structure belonging to a hexagonal crystal system, and further has a multiple of a uniform distribution (MUD) of the {1 1 -2 0} plane obtained by performing a crystal orientation analysis using electron backscatter diffraction (EBSD) of 7.00 to 30.00, and a multiple of a uniform distribution (MUD) of the {0 0 0 1} plane of 15.00 to 90.00. Effect of the Invention

[0011] The inorganic structure according to the present disclosure has a crystal structure belonging to a hexagonal crystal system and is single crystal-like, and therefore can exhibit anisotropy in mechanical properties such as strength and plastic elongation. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a perspective view and a photographic image showing an example of the inorganic structure of the present embodiment. [Diagram 2] Figure 2 shows a pole figure of the {1 1 -2 0} plane created by EBSD measurement. [Diagram 3] Figure 3 shows a pole figure of the {0 0 0 1} plane created by EBSD measurement. [Figure 4] FIG. 4 is a true stress-true strain curve obtained by a compression test of the single-crystal-like inorganic structure of this embodiment. [Diagram 5]FIG. 5 is a graph showing the yield stress (MPa) and plastic elongation (%) of each of the test pieces 1 to 3 obtained based on the true stress-true strain curve of FIG. 4(A). [Figure 6] FIG. 6 is a schematic diagram of an additive manufacturing apparatus used in the manufacturing method of this embodiment. [Figure 7] FIG. 7 is a flow diagram of the method for producing an inorganic structure according to this embodiment. [Figure 8] FIG. 8 is a diagram showing the operation of the layered manufacturing apparatus during the manufacturing process shown in FIG. [Figure 9] FIG. 9 is a diagram showing the operation of the additive manufacturing apparatus in the flow following FIG. [Figure 10] FIG. 10 is a diagram showing the operation of the layered manufacturing apparatus in the flow following FIG. [Figure 11] FIG. 11 is a diagram showing the operation of the additive manufacturing apparatus in the flow following FIG. [Figure 12] FIG. 12 is a diagram showing the operation of the layered manufacturing apparatus in the flow continuing from FIG. [Figure 13] FIG. 13 is a diagram showing the operation of the layered manufacturing apparatus in the flow continuing from FIG. [Figure 14] FIG. 14 is a schematic diagram for explaining the beam scanning direction when the inorganic powder layer is viewed from above in the solidified layer forming step in the flow diagram of the manufacturing process shown in FIG. [Figure 15] FIG. 15 is a diagram showing the relationship between six beam scans, 0° forward, 0° return, 120° forward, 120° return, 240° forward, and 240° return, and the crystal structure belonging to the hexagonal crystal system. [Figure 16] FIG. 16 is a diagram showing the relationship between the beam scanning in the case of only the 0° forward path and the 0° return path and the crystal structure belonging to the hexagonal crystal system. [Figure 17] FIG. 17 is a diagram showing the relationship between the beam scanning in the cases of 0° forward travel, 0° return travel, 90° forward travel, and 90° return travel, and the crystal structure belonging to the hexagonal crystal system. [Figure 18]FIG. 18 is a diagram showing the relationship between the heat flow direction and the crystal orientation of a crystal structure belonging to a hexagonal crystal system when the beam scanning direction in one solidified layer is set to the same angle in both the forward and return directions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The inorganic structure and the method for producing the inorganic structure according to the present embodiment have the following configuration.

[0014] The inorganic structure of the first configuration of the present embodiment is a single-crystal-like inorganic structure having a crystal structure belonging to a hexagonal crystal system. The multiple of a uniform distribution (MUD) of the {1 1 -2 0} plane obtained by performing a crystal orientation analysis on the inorganic structure by electron backscatter diffraction (EBSD) is 7.00 to 30.00, and the MUD of the {0 0 0 1} plane is 15.00 to 90.00.

[0015] The inorganic structure of the first configuration of the present embodiment has a crystal structure belonging to a hexagonal crystal system. Furthermore, in the inorganic compound of the first configuration, the MUD of the {1 1 -2 0} plane, which is an index showing crystal orientation, is 7.00 to 30.00, and the MUD of the {0 0 0 1} plane is 15.00 to 90.00. The inorganic structure of the first configuration that satisfies the above-mentioned MUD is single-crystal-like, where "single-crystal-like" means an inorganic compound that is not a single crystal but exhibits a crystal orientation similar to that of a single crystal. Since the inorganic structure of the first configuration is single-crystal-like, it exhibits moderate anisotropy in mechanical properties such as strength and elongation, compared to polycrystalline inorganic structures having a crystal structure belonging to the hexagonal crystal system, while being able to suppress excessive anisotropy in mechanical properties, as seen in single-crystal inorganic structures.

[0016] The inorganic structure of the second configuration is the inorganic structure of the first configuration and contains, by mass %, 75.0% or more of Mg.

[0017] Magnesium (Mg) is lightweight and has a high specific strength, so the inorganic structure of the second component is lightweight and has a high specific strength, and can also exhibit anisotropy in mechanical properties.

[0018] The inorganic structure of the third aspect is an inorganic compound of the first or second aspect, and has a MUD of the {1 1 -2 0} plane of 8.00 or more.

[0019] In the inorganic structure of the third aspect, the anisotropy of the mechanical properties can be further increased.

[0020] The inorganic structure of the fourth aspect is an inorganic compound of any one of the first to third aspects, and has a MUD of the {0 0 0 1} plane of 18.00 or more.

[0021] In the inorganic structure of the fourth configuration, the anisotropy of the mechanical properties can be further increased.

[0022] The manufacturing method of the inorganic structure of the first configuration is a manufacturing method of the single crystal-like inorganic structure of any one of the first to fourth configurations described above, and includes an inorganic powder layer forming step and a solidified layer forming step. In the inorganic powder layer forming step, an inorganic powder is supplied onto a base to form an inorganic powder layer. In the solidified layer forming step, a beam is scanned on a predetermined selected area of ​​the inorganic powder layer to melt the selected area of ​​the inorganic powder layer to form a solidified layer. In this manufacturing method, the inorganic powder layer forming step and the solidified layer forming step are alternately repeated to stack a plurality of solidified layers, thereby manufacturing an inorganic structure having a crystal structure belonging to a hexagonal crystal system. In the solidified layer forming step, the scanning direction of the beam when forming the solidified layer is set to six directions, 0° forward, 0° return, 120° forward, 120° return, 240° forward, and 240° return, and the scanning direction in each solidified layer is either one of the forward or return directions, or both the forward and return directions at the same angle. Then, the beam is scanned in six different scanning directions at least during the period from the formation of the jth layer (j is a natural number) to the formation of the j+5th layer.

[0023] The manufacturing method of the first configuration of the present embodiment manufactures an inorganic structure of any one of the first to fourth configurations by a so-called additive manufacturing method. At this time, a beam is scanned in six different scanning directions to form a plurality of solidified layers. In this case, when the solidified layer is formed, the crystal structure belonging to the hexagonal crystal system grows stably so that the [1 1 -2 0] orientation of the crystal structure belonging to the hexagonal crystal system is preferentially oriented along the beam scanning direction, and the [0 0 0 1] orientation extends in the stacking direction. As a result, the manufactured inorganic structure becomes single crystal-like and satisfies the above-mentioned range of MUD.

[0024] The second manufacturing method is a manufacturing method for the inorganic structure of the first configuration, and in the solidified layer formation process, the scanning direction of the beam in each solidified layer is in both outward and return directions at the same angle, and of adjacent beam scanning lines, one is the outward direction and the other is the return direction.

[0025] In this case, the growth of the crystal structure belonging to the hexagonal crystal system becomes more stable, and therefore the MUD of the inorganic structure can be further increased.

[0026] The inorganic structure and the method for producing the same according to the present embodiment will be described below. In the drawings, the same or corresponding parts are designated by the same reference numerals and the description thereof will not be repeated.

[0027] [Outline of the inorganic structure according to this embodiment] FIG. 1 is a perspective view and a photographic image showing an example of an inorganic structure 1 according to the present embodiment. Referring to FIG. 1(A), the inorganic structure 1 may be a rectangular solid or hollow material. Also, as shown in FIG. 1(B), the inorganic structure 1 may be a frame-like structure having a plurality of depressions or holes formed on the surface. The inorganic structure 1 may have a shape other than that shown in FIG. 1(A) and (B). The inorganic structure 1 formed by the layered modeling method of the additive manufacturing technology AM described later can be formed into a desired shape.

[0028] The inorganic structure 1 is, for example, a medical device such as a medical implant, a part of a moving body such as an automobile, a mechanical part such as a plant facility, etc. In medical devices, parts of a moving body, mechanical parts, etc., anisotropy of mechanical properties may be required. For example, in the case of a part of a moving body such as an automobile, assuming a collision, it is preferable that the strength in the moving direction of the moving body is higher than in other directions, and high processability is required in directions other than the moving direction.

[0029] [Crystal structure and composition of inorganic structure 1] The inorganic structure 1 is made of an inorganic compound having a crystal structure belonging to a hexagonal crystal system. The symmetry of a crystal structure belonging to a hexagonal crystal system is low. Therefore, if an inorganic structure having a crystal structure belonging to a hexagonal crystal system approaches a single crystal, it is considered that it is easy to express anisotropy in mechanical properties such as strength and plastic elongation. In other words, an inorganic structure having a crystal structure belonging to a hexagonal crystal system can be given high mechanical properties in a specific direction by expressing anisotropy.

[0030] The inorganic compound constituting the inorganic structure 1 is a metal or a ceramic. Examples of metals having a crystal structure belonging to the hexagonal crystal system include magnesium (Mg) metal, titanium (Ti) metal, and zinc (Zn) metal. The inorganic structure 1 is preferably Mg metal. The Mg metal contains 75.0% or more Mg by mass. The lower limit of the Mg content in the Mg metal is preferably 80.0%, more preferably 90.0%, more preferably 95.0%, even more preferably 99.0%, and most preferably 100.0%.

[0031] The Mg metal may contain at least one element selected from the group consisting of Co, Ni, Cu, Zn, Y, Gd, Tb, Dy, Ho, Er, Tm, Ca and Al as an element other than Mg. The Mg metal may contain impurities. For example, the Mg metal may contain 0.10 to 0.50% Ca by mass, with the remainder being Mg, or a metal consisting of Mg and impurities. The Ca content means the total content (mass%) of the Ca content dissolved in the Mg metal matrix and the Ca content in the inclusions and precipitates in the Mg metal matrix. The impurity is, for example, Fe. The Ca content may be 0%. The impurities may also be 0%. An example of a ceramic having a crystal structure belonging to the hexagonal crystal system is alumina (Al2O3).

[0032] [About MUD (Multiple of a Uniform Distribution)] The inorganic structure 1 of this embodiment is single-crystal-like. As described above, single-crystal-like refers to an inorganic compound that is not a single crystal but exhibits a crystal orientation similar to that of a single crystal.

[0033] The degree of single crystal resemblance is indicated by MUD (Multiple of a Uniform Distribution). MUD indicates the ratio of the intensity of the accumulation of a particular crystal orientation to the intensity of the accumulation of a specific crystal orientation when the crystal orientations are distributed randomly. In the case of random distribution, MUD is 1.00.

[0034] The higher the MUD, the higher the degree of accumulation in a specific crystal orientation. In other words, the higher the MUD, the closer the inorganic structure is to a single crystal. If an inorganic structure having a crystal structure belonging to the hexagonal crystal system is a single crystal, the MUD of the {1 1 -2 0} plane is 60.00, and the MUD of the {0 0 0 1} plane is 180.00.

[0035] In inorganic structures 1, MUDs meet two requirements: (Requirement 1) The MUD of the {1 1 -2 0} plane is between 7.00 and 30.00. (Requirement 2) The MUD of the {0 0 0 1} faces is between 15.00 and 90.00. Since the inorganic structure 1 satisfies the above requirements 1 and 2, it is a single-crystal-like structure that is similar to a single crystal.

[0036] [How MUD is measured] The MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane of the inorganic structure 1 are determined by the following method.

[0037] A test piece is taken from the inorganic structure 1. The size of the test piece is not particularly limited. The surface of the test piece is mirror-polished. The mirror-polished surface is used as the observation surface. EBSD measurement is performed on an observation field of 900 μm × 1300 μm of the observation surface, and a pole figure of the {1 1 -2 0} plane and a pole figure of the {0 0 0 1} plane are created.

[0038] The EBSD measurement conditions are as follows: accelerating voltage: 20 kV, working distance: 15 mm, step size: 2 μm, specimen tilt angle: 75°, camera pinning mode: 4 × 4, frame averaging: 1 frame, static background correction: on, automatic background correction: on

[0039] For example, a scanning electron microscope (SEM) equipped with an EBSD detector is used for the EBSD measurement. The EBSD detector is, for example, a NordlysMax (trade name) manufactured by Oxford Instruments Ltd. 3 The scanning electron microscope used is, for example, a JIB-4610F manufactured by JEOL Ltd. The measurement program used is, for example, AztecHKL (Version 4.4) manufactured by Oxford Instruments Ltd.

[0040] Figure 2 shows a pole figure of the {1 1 -2 0} plane in a cross section perpendicular to the beam scanning direction, created by EBSD measurement, and Figure 3 shows a pole figure of the {0 0 0 1} plane in a cross section perpendicular to the beam scanning direction. Based on the obtained pole figure of the {1 1 -2 0} plane, the sum of the intensities within a rectangular region of 10° × 10° centered on {1 1 -2 0} is taken as the density of the {1 1 -2 0} plane. In addition, the density of the {1 1 -2 0} plane in random distribution is calculated. The density of the random distribution is the density of a specific plane ({1 1 -2 0} plane) when the total intensity is uniformly distributed over the entire region of the pole figure. Based on the obtained density of the {1 1 -2 0} plane and the density of the {1 1 -2 0} plane in random distribution, the MUD of the {1 1 -2 0} plane is calculated by the following formula. MUD of {1 1 -2 0} faces = density of {1 1 -2 0} faces / density of {1 1 -2 0} faces in random distribution

[0041] Similarly, based on the obtained pole figure of the {0 0 0 1} plane, the sum of the intensities within a 10° x 10° rectangular region centered on the {0 0 0 1} plane is taken as the density of the {0 0 0 1} plane. Additionally, the density of the {0 0 0 1} plane in the random distribution is calculated. Based on the obtained density of the {0 0 0 1} plane and the density of the {0 0 0 1} plane in the random distribution, the MUD of the {0 0 0 1} plane is calculated using the following formula. MUD of {0 0 0 1} faces = density of {0 0 0 1} faces / density of {0 0 0 1} faces in random distribution

[0042] The above-mentioned MUD calculation using pole figures uses, for example, an analysis program made by Oxford Instruments Ltd. (product name: OXFORD HKL CHANNEL5 (Version 5.12.74.0)). Pole figures are created using the application "Manbo" of the analysis program. When counting the number of data points in a specific direction, Half With is set to 10° as mentioned above. Data Clustering is set to 5°.

[0043] From the above measurements, the MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane are obtained.

[0044] [Characteristics of inorganic structure 1 that meets requirements 1 and 2] As described above, the inorganic structure 1 of this embodiment has a MUD of the {1 1 -2 0} plane of 7.00 or more and 30.00 or less (requirement 1), and a MUD of the {0 0 0 1} plane of 15.00 or more and 90.00 or less (requirement 2). Since the inorganic structure 1 is a single crystal that satisfies requirements 1 and 2, it exhibits moderate anisotropy in mechanical properties (strength and plastic elongation). Furthermore, the inorganic structure 1 of this embodiment can control chemical properties such as solubility and corrosion resistance, and biological properties such as cell adhesiveness and cell activity, depending on the crystal orientation.

[0045] Figure 4 shows the true stress-true strain curve obtained by a compression test of an inorganic structure in which the MUD of the {1 1 -2 0} plane is 9.67 and the MUD of the {0 0 0 1} plane is 26.92. Figure 4 was obtained by carrying out the following test.

[0046] Based on the manufacturing method described below, a single crystal-like inorganic structure was manufactured that was composed of Mg metal (Mg-0.5Ca alloy) with a Ca content of 0.37% by mass and the remainder being Mg, with the MUD of the {1 1 -2 0} plane being 9.67 and the MUD of the {0 0 0 1} plane being 26.92. The density of this inorganic structure was 99.5% or more.

[0047] A test piece was taken from the prepared single crystal-like inorganic structure. The size of the test piece was 2 mm × 2 mm × height 5 mm. As the test pieces, test piece 1 with the height direction of the test piece being oriented in the [0 0 0 1] direction, test piece 2 with the height direction being oriented in the [1 1 -2 0] direction, and test piece 3 with the height direction being oriented in the [1 1 -2 1.85] direction were prepared. The crystal orientations ([0 0 0 1], [1 1 -2 0], [1 1 -2 1.85]) in the crystal structure belonging to the hexagonal crystal system are shown in Figure 4 (B). Using an Instron type compression tester, a compression test was performed on each of the test pieces 1 to 3 at room temperature (25 ° C) in the air, and the true stress-true strain curves shown in Figure 4 (A) were obtained.

[0048] FIG. 5 is a graph showing the yield stress (MPa) and plastic elongation (%) of each of the test pieces 1 to 3 obtained based on the true stress-true strain curve of FIG. 4(A). The bar graph in FIG. 5 shows the yield stress (MPa). The plot of the mark "■" in FIG. 5 shows the plastic elongation (%). With reference to FIG. 4 and FIG. 5, in the inorganic structure 1 satisfying the requirements 1 and 2, anisotropy was observed in the yield strength and plastic elongation in the crystal orientations

[0001] (test piece 1), [1 1 -2 0] (test piece 2), and [1 1 -2 1.85] (test piece 3). Specifically, the yield strength decreased in the order of the compression direction

[0001] , [1 1 -2 0], and [1 1 -2 1.85]. On the other hand, the plastic elongation increased in the compression directions in the order of

[0001] , [1 1 -2 0], and [1 1 -2 1.85].

[0049] As described above, the inorganic structure 1 of the present embodiment exhibits anisotropy in its mechanical properties by satisfying requirements 1 and 2. Therefore, the inorganic structure 1 of the present embodiment can be used as a structure for applications requiring anisotropy in its mechanical properties. For example, the inorganic structure 1 can be used as a medical implant that replaces living bone, or as a mechanical part used in moving bodies such as automobiles or industrial facilities.

[0050] Furthermore, the inorganic structure 1 of this embodiment has reduced anisotropy in mechanical properties compared to a single crystal.

[0051] Table 1 shows the yield strength (MPa) and plastic elongation (%) obtained by compression tests in the [0 0 0 1], [1 1 -2 1.85], and [1 1 -2 0] orientations of Mg single crystals, and the yield strength (MPa) and plastic elongation (%) obtained by compression tests in the [0 0 0 1], [1 1 -2 1.85], and [1 1 -2 0] orientations of the above-mentioned single crystal-like Mg-0.5Ca alloy.

[0052] The yield strength (MPa) and plastic elongation (%) of each crystal orientation of the Mg single crystal were taken from data described in Non-Patent Documents 1 to 3. In these documents, the Mg single crystals were produced by the Bridgman method.

[0053] [Table 1]

[0054] Referring to Table 1, when paying attention to the yield strength (MPa), the Mg-0.5Ca single crystal-like had a smaller difference in yield stress in each crystal orientation compared to the Mg single crystal. Also, in terms of plastic elongation, the Mg-0.5Ca single crystal-like had a smaller difference in plastic elongation in each crystal orientation compared to the Mg single crystal. As a result, the Mg-0.5Ca single crystal-like had a higher plastic elongation than the Mg single crystal in all crystal orientations.

[0055] As described above, the inorganic structure 1 of the present embodiment exhibits anisotropy in mechanical properties compared to a single crystal, but can exhibit high plastic elongation while suppressing the difference in mechanical properties between different crystal orientations. Therefore, the inorganic structure 1 of the present embodiment can obtain moderate anisotropy in mechanical properties.

[0056] In the inorganic structure 1 of this embodiment, the lower limit of the MUD of the {1 1 -2 0} plane is preferably 7.50, more preferably 7.80, more preferably 8.00, more preferably 8.50, and more preferably 9.00. The upper limit of the MUD of the {1 1 -2 0} plane is preferably 25.00, more preferably 20.00, and even more preferably 15.00.

[0057] In the inorganic structure 1 of this embodiment, the lower limit of the MUD of the {0 0 0 1} plane is preferably 15.50, more preferably 16.00, more preferably 17.00, more preferably 18.00, and still more preferably 19.00. The upper limit of the MUD of the {1 1 -2 0} plane is preferably 70.00, more preferably 50.00, more preferably 40.00, and even more preferably 35.00.

[0058] [Method of manufacturing inorganic structure 1] The following describes a method for manufacturing the inorganic structure 1. In the method for manufacturing the inorganic structure 1, for example, the inorganic structure 1 is manufactured by an additive manufacturing method using an additive manufacturing device shown in FIG.

[0059] [Configuration of additive manufacturing device 100] 6, the additive manufacturing apparatus 100 is a beam additive manufacturing apparatus. The additive manufacturing apparatus 100 includes a control device 10, a beam generating device 14, a lens system 15, a mirror (galvanometer mirror) 16, and a chamber 20.

[0060] The beam generator 14 is a high-energy heat source and emits a beam. The beam here is a laser beam or an electron beam. The beam generator 14 is, for example, a solid-state laser such as a fiber laser or a YAG laser, or a CO2 laser. The lens system 15 converges the beam emitted from the beam generator 14 to form the beam 30. The mirror 16 performs irradiation control of the beam 30. In other words, the mirror 16 adjusts the position where the beam 30 is irradiated.

[0061] The chamber 20 includes a bed formation chamber 201 , a powder supply chamber 202 , a modeling table 203 , a piston 204 , and a recoater 205 .

[0062] The bed formation chamber 201 is cylindrical and has an opening at the upper end. The modeling table 203 is stored in the bed formation chamber 201 and supported so as to be movable up and down. The modeling table 203 is raised and lowered by a motor (not shown). A base 208 is placed on the modeling table 203. The base 208 is made of, for example, metal. The inorganic structure 1 is formed on the base 208.

[0063] The powder supply chamber 202 is disposed next to the bed formation chamber 201. The powder supply chamber 202 is cylindrical and includes a piston 204 therein that can move up and down. Inorganic powder 40, which is the starting material for the inorganic structure 1, is layered on the piston 204. As the piston 204 rises, the inorganic powder 40 is discharged from an upper opening of the powder supply chamber 202 and supplied to the bed formation chamber 201.

[0064] The inorganic powder 40 is a metal having a crystal structure belonging to a hexagonal crystal system or a ceramic. The inorganic powder 40 is, for example, a powder of magnesium (Mg) metal, titanium (Ti) metal, zinc (Zn) metal, or the like. The inorganic powder 40 is preferably the above-mentioned Mg metal. When the inorganic powder 40 is a ceramic, the inorganic powder 40 is, for example, alumina.

[0065] The recoater 205 is disposed near the upper opening of the powder supply chamber 202. The recoater 205 is moved in a specific direction (horizontal direction) by a motor (not shown), and reciprocates between the powder supply chamber 202 and the bed formation chamber 201. In Fig. 6, the recoater 205 reciprocates in the L direction.

[0066] The recoater 205 moves in the L direction, thereby moving the inorganic powder 40 discharged from the powder supply chamber 202 in the horizontal direction and supplying it to the bed formation chamber 201. The inorganic powder 40 deposited on the base 208 of the modeling table 203 in the bed formation chamber 201 forms an inorganic powder layer 206. The recoater 205 moves in the L direction, thereby moving the inorganic powder 40 in the horizontal direction, and the surface of the inorganic powder layer 206 is made flat.

[0067] A roller may be used instead of the recoater 205. When a roller is used, the inorganic powder layer 206 can be formed while optionally applying pressure to the inorganic powder 40 with the roller.

[0068] The control device 10 includes a central processing unit (CPU), not shown, a memory, and a storage device such as a HDD or SSD. Well-known CAD (Computer Aided Design) applications and CAM (Computer Aided Manufacturing) applications are stored in the storage device.

[0069] The control device 10 uses a well-known CAD (Computer Aided Design) application to set the three-dimensional shape of the inorganic structure 1 to be manufactured. The control device 10 further uses a CAM application to set processing conditions based on the set three-dimensional shape. In the additive manufacturing method, the inorganic structure 1 is manufactured by stacking multiple solidified layers formed by the beam 30. The processing conditions include the processing conditions when each solidified layer is formed. The control device 10 controls the beam generator 14, the lens system 15, and the mirror 16 based on the processing conditions to adjust the energy density, scanning pattern, beam irradiation position, etc. of the beam 30.

[0070] [About the manufacturing process] The method for producing the inorganic structure 1 of this embodiment uses an additive manufacturing method to produce a single crystal-like inorganic structure 1. The production method of this embodiment includes an inorganic powder layer forming step and a solidified layer forming step.

[0071] In the inorganic powder layer forming step, the inorganic powder 40 is supplied onto the base 208 to form the inorganic powder layer 206 . In the solidified layer forming step, the beam 30 is scanned over a predetermined selected area of ​​the inorganic powder layer 206 to melt and solidify the selected area of ​​the inorganic powder layer 206, thereby forming a solidified layer.

[0072] In the manufacturing method of this embodiment, the above-mentioned inorganic powder layer forming process and solidified layer forming process are alternately repeated to stack multiple solidified layers, from the first layer to the kth layer (k is a natural number), to produce a single-crystal-like inorganic structure 1 having a crystal structure belonging to a hexagonal crystal system.

[0073] 7 is a flow diagram of the manufacturing process of the inorganic structure 1 of this embodiment. The manufacturing method of the inorganic structure 1 including the inorganic powder layer forming step and the solidified layer forming step will be described below with reference to FIG.

[0074] Referring to FIG. 7, the control device 10 first starts the formation of a solidified layer SL1 which is the first layer and is the lowest layer.

[0075] When the irradiated beam 30 is a laser beam, an inert gas (argon, nitrogen, helium, or the like) is supplied into the chamber 20, and the base 208 arranged on the modeling table 203 is preheated. During preheating, the base 208 may be preheated without supplying an inert gas after drawing a vacuum. Alternatively, the base 208 may be preheated after supplying an inert gas without drawing a vacuum. The base 208 may be preheated at all times during the manufacturing process. Alternatively, the base 208 does not need to be preheated. When the irradiated beam 30 is an electron beam, preheating is not performed as in the case of laser light, but is performed by another method, which will be described later when the irradiated beam 30 is an electron beam.

[0076] [Inorganic powder layer formation process (S21)] Next, the control device 10 forms an inorganic powder layer 206 (inorganic powder layer forming step: S21). The control device 10 instructs the piston 204 of the powder supply chamber 202 to rise and discharge the inorganic powder 40 that is the starting material of the inorganic structure 1. The powder supply chamber 202 discharges the inorganic powder 40 in response to the instruction from the control device 10. At this time, as shown in FIG. 8, the recoater 205 moves in the L direction. As a result, the discharged inorganic powder 40 moves in the L direction and is supplied to the bed formation chamber 201. The inorganic powder 40 is deposited on the base 208 and the modeling table 203, and the inorganic powder layer 206 is formed.

[0077] The recoater 205 further moves horizontally (in the L direction) on the surface of the inorganic powder layer 206 on the base 208. At this time, the inorganic powder 40 moves in the horizontal direction. The thickness of the inorganic powder layer 206 is not particularly limited, but is, for example, 20 to 100 μm.

[0078] When the irradiated beam 30 is an electron beam, after the inorganic powder layer 206 is formed, the inorganic powder layer 206 is preheated (S23). Preheating can be performed by various methods. For example, the inorganic powder layer 206 is preheated by irradiating the beam 30 to the inorganic powder layer 206. After the preheating, the solidified layer forming step (S22) is performed.

[0079] [Coagulated layer formation step (S22)] 9, based on preset beam scanning conditions, the inorganic powder layer 206 is scanned with the beam 30 to melt a predetermined selected region in the inorganic powder layer 206 and form a solidified layer SL1 of a first layer (solidified layer forming step: S22). The control device 10 reads out processing condition data for the solidified layer SL1 of the first layer from the memory among the multiple processing condition data. Based on the read processing condition data, the control device 10 controls the beam 30. The processing conditions also include information on the region (selected region) in the inorganic powder layer 206 to be melted.

[0080] Specifically, the control device 10 scans a predetermined selected region in the solidified layer SL1 with the beam 30 using a preset beam scanning path (beam scanning conditions). The selected region irradiated with the beam 30 melts and then solidifies. As a result, a solidified layer SL1 is formed in the selected region, as shown in FIG. 9. At this time, the inorganic powder 40 arranged in the region of the inorganic powder layer 206 other than the solidified layer SL1 (selected region) (i.e., the region other than the selected region) does not melt.

[0081] After the first solidified layer SL1 is formed, the control device 10 judges whether the formed solidified layer SL is the uppermost solidified layer (S23). The information on the three-dimensional shape of the inorganic structure 1 registered in the control device 10 includes information on the three-dimensional shapes and processing conditions related to the solidified layers SL1 to SLk (k is a natural number) of the uppermost solidified layer. Based on this information, the control device 10 judges whether the formed solidified layer SL is the uppermost solidified layer SLk.

[0082] If the formed solidified layer SL is not the final solidified layer SLk (NO in S23), the control device 10 prepares to produce the second solidified layer SL2. Specifically, the control device 10 lowers the modeling table 203 by the layer pitch Δh (S24). As a result, as shown in FIG. 10, the surface of the inorganic powder layer 206 is lowered by Δh compared to FIG. 9.

[0083] After step S24 is completed, the process returns to step S21. At this time, the control device 10 forms a new inorganic powder layer 206 on the inorganic powder layer 206 on which the solidified layer SL1 has been formed (S21). Specifically, in response to an instruction from the control device 10, the piston 204 in the powder supply chamber 202 rises, and the inorganic powder 40 is discharged again. At this time, as shown in FIG. 11, the recoater 205 moves in the L direction. Therefore, the inorganic powder 40 moves in the L direction to form a new inorganic powder layer 206 having a thickness Δh. The surface of the new inorganic powder layer 206 is smoothed flat by the recoater 205.

[0084] Next, the control device 10 forms the solidified layer SL2 of the second layer (S22). At this time, the control device 10 irradiates the inorganic powder layer 206 with the beam 30 based on the processing condition data of the solidified layer SL2 of the second layer. As a result, as shown in FIG. 12, the inorganic powder layer 206 in the selected area irradiated with the beam 30 melts and solidifies, forming the solidified layer SL2. Through the above steps, the solidified layer SL2 is laminated on the solidified layer SL1.

[0085] Next, the process proceeds to step S23, where the control device 10 repeats the operations of steps S21 to S24 until the uppermost solidified layer SLk is formed. That is, the control device 10 repeats the inorganic powder layer forming step (S21) and the solidified layer forming step (S22) to stack a plurality of solidified layers SL until the inorganic structure 1 having a desired three-dimensional shape is completed as shown in FIG.

[0086] The shape of the solidified layer SLj (j is a natural number from 1 to k) is not restricted by the shape of the underlying solidified layer SLj-1, and can be larger or smaller than the solidified layer SLj-1. Furthermore, the shape of the solidified layer SLj can have one or more gaps. In this case, the inorganic structure 1 can have a shape that cannot be obtained by normal cutting, such as a closed space or a complex hole shape.

[0087] As described above, in the manufacturing method of this embodiment, the inorganic powder layer forming step (S21) and the solidified layer forming step (S22) are repeatedly performed to stack multiple solidified layers SL to produce an inorganic structure 1 having a crystal structure belonging to a hexagonal crystal system.

[0088] [Beam scanning direction in the solidified layer formation process] 14 is a schematic diagram for explaining the scanning direction of the beam 30 when the inorganic powder layer 206 is viewed in plan in the solidified layer forming step. In the manufacturing method of this embodiment, as shown in FIG. 14, the scanning direction of the beam 30 when forming the solidified layer SL in the solidified layer forming step (S22) is set to six directions: 0° forward, 0° return, 120° forward, 120° return, 240° forward, and 240° return. Here, 120° and 240° mean the relative angle when the beam scanning line (scanning direction) at 0° is used as the reference axis. The reference axis of 0° when the inorganic powder layer 206 is viewed in plan can be determined arbitrarily.

[0089] Furthermore, the scanning direction during the formation of each solidified layer SL is either one of the forward or backward directions, or both the forward and backward directions at the same angle. Then, the beam is scanned in all six scanning directions at least from the formation of the jth layer (j is a natural number) solidified layer SLj to the formation of the j+5th layer solidified layer SLj+5. By adjusting the scanning direction in this way and stacking multiple solidified layers SL, a single-crystal-like inorganic structure 1 with a crystal structure belonging to a hexagonal crystal system that satisfies requirements 1 and 2 can be manufactured. This point will be explained below.

[0090] Fig. 15 is a diagram showing the relationship between six beam scans, i.e., a 0° forward path, a 0° return path, a 120° forward path, a 120° return path, a 240° forward path, and a 240° return path, and the crystal structure belonging to the hexagonal crystal system. Fig. 15 is a plan view of the inorganic powder layer 206.

[0091] For example, assume that the scanning direction of solidified layer SLj of the jth layer is 0° outward, the scanning direction of solidified layer SLj+1 of the j+1th layer is 120° outward, the scanning direction of solidified layer SLj+2 of the j+2th layer is 240° outward, the scanning direction of solidified layer SLj+3 of the j+3th layer is 0° return, the scanning direction of solidified layer SLj+4 of the j+4th layer is 120° return, and the scanning direction of solidified layer SLj+5 of the j+5th layer is 240° return, and this combination is repeated to stack multiple solidified layers.

[0092] In each solidified layer SLj formed in the solidified layer formation process, the heat flow direction HF is inclined by 60° with respect to the scanning direction during scanning of the beam 30. Along this heat flow direction HF, the [1 1 -2 0] orientation tends to be preferentially oriented. As a result, the [1 1 -2 0] orientation also tends to be oriented in the beam scanning direction, and the

[0001] orientation (C-axis) tends to be oriented in the stacking direction.

[0093] In the formation of the solidified layer SLj in each of the jth layer to the j+5th layer, as described above, the [1 1 -2 0] orientation is preferentially oriented along the beam scanning direction, and the

[0001] orientation is preferentially oriented along the stacking direction. As a result, by the time the solidified layers SLj to SLj+5 of the jth layer to the j+5th layer are formed, the crystal growth is constrained to six directions of the [1 1 -2 0] orientation by six beam scans of 0° forward, 0° return, 120° forward, 120° return, 240° forward, and 240° return. Therefore, the crystal grows so that the orientation difference of the crystal growing from the six directions is minimized. As a result, the preferential orientation of the [1 1 -2 0] orientation along the 0°, 120°, and 240° directions is stabilized. Through the above process, the inorganic structure 1 manufactured satisfies requirements 1 and 2 and becomes single crystal-like.

[0094] On the other hand, as shown in FIG. 16, the case where the beam scanning direction is only 0° forward and 0° return is assumed. For example, assume that the beam scanning direction is 0° forward in the jth layer of solidified layer SLj, and 0° return in the j+1th layer of solidified layer SLj+1, and this is repeated to stack multiple solidified layers SL. In this case, crystal growth is restricted to only two directions. Therefore, there is insufficient restriction, and the crystal orientation is not stable. As a result, the manufactured inorganic structure 1 does not satisfy requirement 1 and / or requirement 2, and is difficult to become single crystal-like.

[0095] 17, a 0° forward path, a 0° return path, a 90° forward path, and a 90° return path are assumed. For example, assume that the beam scanning direction is 0° forward in the solidified layer SLj of the jth layer, the beam scanning direction is 90° forward in the solidified layer SLj+1 of the j+1th layer, the beam scanning direction is 0° return in the solidified layer SLj+2 of the j+2th layer, and the beam scanning direction is 90° return in the solidified layer SLj+3 of the j+3th layer, and this is repeated to stack a plurality of solidified layers SL.

[0096] In this case, in the 0° direction, the [1 1 -2 0] orientation grown by 0° forward and 0° return beam scanning competes with the [1 0 -1 0] orientation grown by 90° forward and 90° return beam scanning. Furthermore, in the 90° direction, the [1 0 -1 0] orientation grown by 0° forward and 0° return beam scanning competes with the [1 1 -2 0] orientation grown by 90° forward and 90° return beam scanning. Therefore, the crystal orientation is not stable. As a result, the manufactured inorganic structure 1 does not satisfy requirement 1 and / or requirement 2, and is difficult to become single crystal-like.

[0097] As described above, in this embodiment, the beam scanning direction in the solidified layer forming step is set to six directions: 0° forward, 0° return, 120° forward, 120° return, 240° forward, and 240° return. The beam is scanned in all six scanning directions at least from the formation of the jth solidified layer SLj to the formation of the j+5th solidified layer SLj+5. By repeating this combination of beam scanning directions to stack multiple solidified layers, a single-crystal-like inorganic structure 1 having a crystal structure belonging to a hexagonal crystal system that satisfies requirements 1 and 2 can be manufactured.

[0098] If the beam scanning is not performed at the same angle in the forward and backward directions, but only one direction (forward or backward) at one angle (0°, 120° or 240°), the inorganic structure 1 of this embodiment cannot be manufactured. For example, assume that only the forward direction is performed in the beam scanning at 0°, 120°, and 240°, and the backward direction is not performed. In such a case, for example, the beam scanning direction when forming the solidified layer SLj of the jth layer is set to 0° forward direction, the beam scanning direction when forming the solidified layer SLj+1 of the j+1th layer is set to 120° forward direction, and the beam scanning direction when forming the solidified layer SLj+2 of the j+2th layer is set to 240° forward direction, and this combination of beam scanning directions is repeatedly performed in the formation of the solidified layer SL of the j+4th layer and after. In this case, only the three directions of the [1 1 -2 0] orientation are restricted. Therefore, the preferred orientation of the [1 1 -2 0] orientation is not stable. As a result, an inorganic structure 1 satisfying requirements 1 and 2 is not formed, and the MUD on the {1 1 -2 0} plane and / or the MUD on the {0 0 0 1} plane do not satisfy requirements 1 and / or 2.

[0099] In addition, the order of the beam scanning directions is not particularly limited as long as all of the above six beam scannings are performed from the formation of the jth solidified layer SLj to the formation of the j+5th solidified layer SLj+5. For example, the beam scanning directions when forming each solidified layer SLj may be determined in the order shown in Case 1 to Case 9 in Table 2.

[0100] [Table 2]

[0101] Furthermore, as shown in Cases 10 and 11 of Table 2, forward and return passes at the same angle may be performed in one layer. For example, in Case 10, the beam is scanned in both directions, 0° forward and 0° return, for the solidified layer SLj of the jth layer. In this case, all six beam scanning directions have been performed when the solidified layers SLj to SLj+4 of the jth to j+4th layers have been formed.

[0102] In case 11 of Table 2, bidirectional beam scanning at the same angle is performed on the jth solidified layer SLj and the j+1th solidified layer SLj+1. In this case, when the jth to j+3th solidified layers SLj to SLj+3 are formed, all six beam scanning directions have been performed.

[0103] [Preferred beam scanning direction] Preferably, the scanning direction of the beam in each solidified layer SL is bidirectional, forward and backward, at the same angle, and between adjacent beam scanning lines, one is the forward path and the other is the backward path.

[0104] For example, in the jth layer, the beam scanning direction is bidirectional, 0° forward and 0° backward, and for adjacent beam scanning lines, one is the forward path and the other is the backward path. In other words, forward beam scanning and backward beam scanning are performed alternately. In the j+1th layer, the beam scanning direction is bidirectional, 120° forward and 120° backward, and for adjacent beam scanning lines, one is the forward path and the other is the backward path. In the j+2th layer, the beam scanning direction is bidirectional, 240° forward and 240° backward, and for adjacent beam scanning lines, one is the forward path and the other is the backward path. The above combinations of beam scanning directions are repeated to stack multiple solidified layers SL to manufacture the inorganic structure 1.

[0105] As shown in Fig. 18, the beam scanning direction in the solidified layer SLj is set to be in both directions, forward and backward, at the same angle. In Fig. 18, as an example, it is set to be in both directions, 0° forward and 0° backward. In addition, one (BL1) of the adjacent beam scanning lines BL1 and BL2 is set to be 0° forward, and the other (BL2) is set to be 0° backward. In this case, the heat flow direction HF on the forward path (solid line in the figure) and the heat flow direction HF on the return path (dashed line in the figure) are parallel. In this case, the [1 1 -2 0] orientation grows more stably. As a result, assuming that six combinations of beam scanning are performed, namely, 0° forward path, 0° return path, 120° forward path, 120° return path, 240° forward path, and 240° return path, the [1 1 -2 0] orientation is likely to grow stably along the beam scanning direction. As a result, the manufactured inorganic structure 1 satisfies requirements 1 and 2, and is more likely to be single-crystal-like. EXAMPLES

[0106] Inorganic structures were manufactured by changing the combination of beam scanning directions in the additive manufacturing method. The MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane of the manufactured inorganic structures were obtained.

[0107] Specifically, Mg-0.5Ca metal powder (an alloy containing 0.37% by mass of Ca with the remainder being Mg) was prepared as the inorganic powder. Based on the above-mentioned additive manufacturing method, the inorganic powder layer forming process and the solidified layer forming process were repeated to stack multiple solidified layers to manufacture an inorganic structure. The manufactured inorganic structure was a structure made of Mg-0.5Ca metal. Processing conditions other than the beam scanning direction were the same for all test numbers. The laser energy density was 50 J / mm 3 The inorganic structure for each test number was a cube of 5 mm x 5 mm x 5 mm.

[0108] The combination of beam scanning directions for each test number was as shown in Table 3. For example, test numbers 1 to 9 in Table 3 mean that the beam scanning direction pattern of the jth layer to the j+5th layer was repeatedly performed to form multiple solidified layers SL. Test number 10 means that the beam scanning direction pattern of the jth layer to the j+2th layer was repeatedly performed to form multiple solidified layers SL. Test number 11 means that the beam scanning direction pattern of the jth layer was repeatedly performed to form multiple solidified layers SL. Test number 12 means that the beam scanning direction pattern of the jth layer to the j+1th layer was repeatedly performed to form multiple solidified layers SL.

[0109] [Table 3]

[0110] The MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane of the inorganic structure manufactured for each test number were determined according to the above-mentioned [MUD measurement method]. The obtained MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane are shown in Table 3.

[0111] Referring to Table 3, the MUD of the {1 1 -2 0} plane was 7.00 or more and 30.00 or less, and the MUD of the {0 0 0 1} plane was 15.00 or more and 90.00 or less in all of the test numbers 1 to 9. Therefore, all of these inorganic structures were single crystal-like.

[0112] Furthermore, in test numbers 4 to 9, the scanning direction of the beam in each solidified layer was set to the same angle in both directions, forward and backward. Therefore, the MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane of the inorganic structures of these test numbers were higher than the MUD of the {1 1 -2 0} plane and the MUD of the {0 0 0 1} plane of the inorganic structures of test numbers 1 to 3.

[0113] On the other hand, in test number 10, only the forward beam scanning was performed at 0°, 120°, and 240°, and the return beam scanning was not performed. Therefore, the MUD of the {1 1 -2 0} plane of the manufactured inorganic structure was less than 7.00.

[0114] In test number 11, only the forward and backward beam scan directions of 0° were repeatedly performed, and therefore the MUD of the {1 1 -2 0} plane of the produced inorganic structure was less than 7.00.

[0115] In test number 12, beam scanning was repeatedly performed at 0° forward, 0° backward, 90° forward, and 90° backward. As a result, the MUD of the {1 1 -2 0} plane of the manufactured inorganic structure was less than 7.00.

[0116] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure. [Explanation of symbols]

[0117] 1 Inorganic structures

Claims

1. A single crystal-like inorganic structure, It has a crystal structure belonging to the hexagonal crystal system, The multiple of a uniform distribution (MUD) of the {1 1 -2 0} plane obtained by performing a crystal orientation analysis using electron backscatter diffraction (EBSD) is 7.00 or more and 30.00 or less, and the multiple of a uniform distribution (MUD) of the {0 0 0 1} plane is 15.00 or more and 90.00 or less. Inorganic structures.

2. The inorganic structure according to claim 1 , The chemical composition contains 75.0% or more Mg by mass%, Inorganic structures.

3. The inorganic structure according to claim 1 , The MUD of the {1 1 -2 0} plane is 8.00 or more; Inorganic structures.

4. The inorganic structure according to claim 1 , The MUD of the {0 0 0 1} plane is 18.00 or more; Inorganic structures.

5. A method for producing the single-crystal-like inorganic structure according to claim 1, comprising the steps of: an inorganic powder layer forming step of supplying an inorganic powder onto a base to form an inorganic powder layer; a solidified layer forming step of scanning a beam on a predetermined selected area of ​​the inorganic powder layer to melt the selected area and form a solidified layer; and alternately repeating the steps to stack a plurality of the solidified layers to produce the inorganic structure having a crystal structure belonging to the hexagonal crystal system. In the solidified layer forming step, The scanning direction of the beam when forming the solidified layer is set to six directions, namely, 0° forward, 0° return, 120° forward, 120° return, 240° forward, and 240° return, and the scanning direction in each solidified layer is set to one of the forward and return directions, or both the forward and return directions at the same angle; The beam is scanned in the six scanning directions at least during the period from the formation of a solidified layer of a jth layer (j is a natural number) to the formation of a solidified layer of a j+5th layer. A method for manufacturing an inorganic structure.

6. A method for producing an inorganic structure according to claim 5, In the solidified layer forming step, The scanning direction of the beam in each solidified layer is bidirectional, that is, forward and backward, at the same angle, and in adjacent beam scanning lines, one is the forward path and the other is the backward path. A method for manufacturing an inorganic structure.

Citation Information

Patent Citations

  • Shock absorbing structure and method of manufacturing the same

    JP2011136083A

  • Method for manufacturing structure and structure

    JP2013094390A

Cited By

  • Semiconductor device

    CN122784132A